How do I evaluate texts? Reflections about the way of thinking and doing of language undergraduates - Gustavo Henrique da Silva Lima; Dennys Dikson (Working Papers em Linguística, 2015)
http://dx.doi.org/10.5007/1984-8420.2015v16n2p210